Eyelid Gnathostomiasis Presenting as an Orbital Mass: A Case Report of Rare Presentation - Rojdamrongrantana, Duangmontree; Warnnissorn, Naree; Muangsiri, Sirineen; Pincome, Nutdanai; Trarungreang, Pimpakarn (Asian Medical Journal and Alternative Medicine, 2022)
A 25-year-old female presented with a three-week history of mass in the left lower orbit. On examination, a well-circumscribed rubbery round mass protruding from the left lower eyelid was noted. An anterior orbitotomy was performed via transconjunctival approach. Ultimately, the diagnosis of gnathostomiasis was done pathologically.